Characterisation of RNA uridylyltransferases in schizosaccharomyces pombe - Scott, D (2012)
The control of RNA stability and function via 3' end modification is a widely conserved and biologically important regulatory mechanism. Though this control has traditionally been considered to depend entirely on the addition or removal of long or short poly(A) tails, in recent years the post-transcriptional addition of uridylyl residues to the 3' ends of diverse RNAs has been identified as a physiologically relevant degradative signal in a range of different species. The Schizosaccharomyces pombe protein Cid1 has been previously shown to possess uridylylation activity on mRNAs and via this uridylylation to promote the decapping and degradation of mRNAs. This work investigates the presence of residual uridylylation activity in strains lacking the cid1 uridylyltransferase and shows that a second S. pombe enzyme, cid16, possesses robust and highly specific poly(U) polymerase (PUP) activity in vitro and is able to uridylylate the act1 mRNA in vivo Characterisation of Cid16 shows that it possesses greater processivity and selectivity than Cid1 both for RNA substrates and for UTP, suggesting that Cid16 is a more stringent PUP than is Cid1. Deletion of cid16 causes few changes in mRNA levels during exponential growth, suggesting that cid16 may act on other targets or during other phases of the S. pombe life cycle, including a potential role in the regulation of RNAi factors during meiosis. Separate experiments show that, while cid1 is dispensable for the stability of most RNAs during exponential growth, it unexpectedly regulates the transcription of genes in extended subtelomeric regions of the S. pombe genome, suggesting a hitherto unknown role for cid1 in the regulation of subtelomeric heterochromatin formation and/or propagation. These observations suggest that the process of uridylylation in S. pombe is significantly more complicated than previously suspected and may regulate a range of different targets in diverse biological pathways.